RASIO KEUANGAN DAN HARGA SAHAM SYARIAH: PERAN MODERASI EPS DALAM INDEKS ISLAM JAKARTA - RAMADAHNIEL ISLAMI; MUHAMMAD YUSUF; EVA ULFAH RAHAYU (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
This study utilizes secondary data sourced from the official website of the Indonesia Stock Exchange (IDX) and Investing. The study population includes all companies listed in the Jakarta Islamic Index (JII) during the 2016–2018 period. The study sample consisted of 18 companies listed on the Indonesia Stock Exchange, specifically those included in the JII index during that period. The data analysis methods used include the classical assumption test and Moderated Regression Analysis (MRA), also known as the interaction test. The results show that partially the variables DER, DPR, ROA, and PBV have a significant effect on sharia stock prices, while the variables PER, CR, NPM, and DYR do not show a significant effect. Furthermore, the moderating variable Earning Per Share (EPS) is proven to moderate the relationship between the independent and dependent variables, and strengthens the Influence of the independent variable on sharia stock prices